SLR : SYSTEMATIC LITERATURE REVIEW EFEKTIVITAS PENGGUNAAN APLIKASI DESMOS TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MTEMATIS SISWA - Restu Sulistiowati, Marlina; Heni Pujiastuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of the use of the Desmos application in mathematics learning on students’ mathematical conceptual understanding through a Systematic Literature Review (SLR) approach. The method used refers to the stages of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), which include identification, screening, eligibility, and inclusion. The data sources were obtained from scientific articles published between 2019 and 2024 through databases such as Google Scholar, ERIC, and ScienceDirect. The selected articles were determined based on predefined inclusion and exclusion criteria. The results of the review indicate that the use of Desmos in mathematics learning has a positive impact on students’ mathematical conceptual understanding. In addition, the use of Desmos also enhances students’ motivation and engagement in the learning process. Therefore, Desmos can be used as an effective learning medium to improve students’ conceptual understanding in mathematics.